PARADIGMA AKUNTANSI SYARIAH DI INDONESIA - Ziyadatin Ilmi, Anugrahi Putri; Latifah, Eny (JIAR : Journal Of International Accounting Research, 2022)
The purpose of this article is to examine the extent to which accounting practices in financial institutions or companies in Indonesia comply with sharia principles. Research methods with case studies on financial institutions or certain companies can be used to explore existing sharia accounting practices and analyze the extent to which these institutions comply with sharia principles. This research can involve analysis of regulations, standards, financial reports and literature related to sharia accounting. in Indonesia by discussing accounting paradigms, research paradigms, developments, definitions of accounting. Research can produce findings about the extent to which accounting and financial reporting practices in Indonesia comply with sharia principles. Research can increase understanding of how sharia accounting is implemented and regulated in Indonesia.